U-U and Th-U ages over the last 820,000 years from Devils Hole calcite (NV, USA) for palaeo water table reconstruction - Steidle, Simon Dominik; Wendt, Kathleen A; Dublyansky, Yuri; Edwards, R Lawrence; Li, Xianglei; McClure, Gracelyn; Moseley, Gina Elaine; Spötl, Christoph (PANGAEA, 2024)
U-series measurements to constrain the age of Devils Hole cave 2's submerged calcite (Nevada, USA). Samples originate from 11 horizontally drilled cores of 0.1 to 1.3m length and 2.5cm diameter. They were taken from the hanging wall at elevations between +3.2 m and +19.5 m relative to the modern water table. Sampling was done between the years 2015 and 2023. A resurvey of the elevation of all sample locations was done in 2023. Samples for dating are all taken from mammillary calcite which precipitates from the groundwater underneath the water table. The sequence of mammillary calcite and Folia which only grows at the water table surface allow to reconstruct a water table history. Depending on the sequence of mammillary calcite and Folia, samples represent the following types: (i) the water table increased above this elevation, (d) the water table decrease to below this elevation, (b) water table rose briefly above this elevation and then dropped below it again, (x) water table was above this elevation (see method section of Steidle et al. (2024) for details). Both, 230Th/U ages and 234U/U ages were calculated. The latter method could be applied under the assumption that initial 234U/U concentration are correlated with d18O and d13C stable isotope ratios (Li et al., 2021). The ages range from 820,000 to 350,000 years ago and show that the water table oscillations are in sync with global climate shifts where Interglacials are marked by a low water table and vice versa glacials are marked by a high water table (Steidle et al., 2024).
Keywords: Devils Hole; Great Basin; groundwater table; palaeoclimate; speleothem; Th-U ages